Role and Timing of Counselling in the Treatment of Severe Mental - Health Disorders: Implications for Counselling - Jamila YUSUF; Habibat Bolanle ABDULKAREEM; Kafayat Toyin ARABA; Mustapha Shina Ahmed (Universitas Pendidikan Ganesha, 2025)
Severe mental health disorders remain a global concern due to delayed treatment and the lack of optimal integration between pharmacological and psychosocial interventions, particularly regarding limited understanding of the appropriate role and timing of counseling in supporting long-term recovery. This study aims to analyze, evaluate, and synthesize the role and timing of counseling interventions. A qualitative approach with a conceptual–integrative design in the form of a position paper was employed. The study examined 45 scientific and policy documents, including peer-reviewed journal articles, clinical practice guidelines, reports from global health organizations, and empirical studies on pharmacological and psychosocial interventions. Data were collected through a document analysis method using a structured document analysis matrix as the research instrument, developed based on intervention focus, counseling timing, and recovery outcomes. Data analysis was conducted using thematic and comparative analysis to identify patterns, relationships, and conceptual gaps within the literature. The findings indicate that early and continuous counseling following pharmacological stabilization is more effective in enhancing psychosocial functioning and supporting long-term recovery. The timing and continuity of counseling are key elements in managing severe mental disorders, highlighting the need for early detection, multidisciplinary collaboration, and adaptive counseling models.